Inclusion of Salicornia ramosissima biomass in diets for juvenile whiteleg shrimp (Penaeus vannamei) induces favourable but transient effects in the immune and oxidative status - Ramos-Pinto, Lourenço; Marçal, Raquel; Barreto, André; Laranjeira, Adriana; Machado, Marina; Fernández-Boo, Sérgio; Teixeira, Carla; Oliveira, Joana; Couto, Ana; Dias, Jorge; Guilherme, Sofia; Veríssimo, Ana C. S.; et al. (Frontiers in Marine Science, 2024)
The whiteleg shrimp, Penaeus vannamei, is a highly valued and globally produced crustacean species. However, the rising cost of shrimp feed, exacerbated by increasing cereal prices, prompts the exploration of cost-effective and sustainable formulations. This study investigates the potential of Salicornia ramosissima biomass by-product (the non-edible part) as a substitute for wheat meal in juvenile shrimp diets, aiming to create sustainable formulations.Particularly to assess the impact of incorporating S. ramosissima into shrimp aquafeeds on various aspects of shrimp development, including growth performance, survival, immune status, and oxidative status. A commercial-like diet was formulated and served as control, whereas four other diets contained S. ramosissima stems or a combination of leaves and seeds, both at inclusion levels of 5% and 10%. Shrimps were fed the experimental diets for 31 and 55 days, followed by a bacterial bath challenge test to gauge their immune response to pathogens. At the end of the feeding period, growth performance and survival rates remained consistent across all diets. However, shrimp fed diets with S. ramosissima consumed more feed to achieve similar weights of those fed the control diet, particularly in diets containing leaves and seeds at a 10% inclusion level, likely due to lower digestibility of dry matter, lipids, and energy.While S. ramosissima biomass inclusion did not affect shrimp weight, relative growth rate, or survival, it did lead to higher feed conversion ratios and feed intake. Additionally, S. ramosissima inclusion affected shrimps' overall body composition, particularly moisture and ash content. S. ramosissima inclusion modulated antioxidant enzyme activity in the shrimp's hepatopancreas, indicating potential health improvements. The observed gene expression changes related to antioxidant enzymes, points to an overall down-regulation with the inclusion of S. ramosissima. Despite challenges in feeding efficiency, the inclusion of S. ramosissima, especially stems, shows promise in reducing feed costs by utilizing a food agro-industrial byproducts (non edible parts). Furthermore, S. ramosissima inclusion led to subtle changes in certain plasma humoral parameters. In conclusion, this study highlights the potential of this halophyte as a functional feed ingredient capable of enhancing shrimp's antioxidant response, aligning with global resource optimization and sustainability initiatives.